PKM Pelatihan Manajemen Kepemimpinan dalam Meningkatkan Skill Berorganisasi Siswa - Muhammad Ainul Yaqin; Eka Diana; Moh. Rofiki; Zainul Ilyas; Muhammad Irfan Efendi; Alif Al Mahdi (Lembaga Pengembangan Kinerja Dosen, 2024)
This training aims to develop the organizational skills of MA Badridduja student council through a structured, hands-on approach. The program is designed to provide theoretical understanding as well as practical skills that students can apply in their daily lives. Interactive methods such as group discussions, simulations, and role-playing are used to help students understand the concept of leadership and how to apply it in an organizational context. Careful preparation prior to implementation, such as information dissemination, preparation of training materials, and coordination with relevant parties, were key to the success of this training. The implementation phase included initial evaluation and delivery of training materials. The final evaluation showed significant improvement in students' abilities in leadership and organizational skills. The results of this training show that students not only get direct benefits in the development of leadership skills and organizational skills. In addition, it also provides a solid foundation for students' academic success and prepares them to become competent and influential future leaders in society.